2006
DOI: 10.3917/spub.063.0389
|View full text |Cite
|
Sign up to set email alerts
|

Prévalence de l'obésité chez l'enfant et l'adolescent scolarisés en Seine Saint-Denis

Abstract: In France, the increase of obesity prevalence in children constitutes a true "epidemic". The school doctors based in Seine Saint-Denis carried out a study during the 2003-2004 academic year on the prevalence of childhood obesity in students from nursery school and junior high school. It was also closely linked to an individually-based awareness campaign for better management of the students surveyed and selected. The results show a prevalence of obesity of 13.9% at 6 years old and 14.3% at 15 years, values whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Moreover, snacking has been related with other behaviors, such as TV watching, which are all believed to be, by itself, obesogenic; in this way, a pattern of potentially unhealthy behaviors has been described, identifying snacking children as having a sedentary lifestyle and spending the majority of leisure time alone [9]. However, snacking is also related with social and group activities, as an accompanying activity during social meetings and after them [10]. Social pattern of interaction are of course very different when referred to adults than for children.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, snacking has been related with other behaviors, such as TV watching, which are all believed to be, by itself, obesogenic; in this way, a pattern of potentially unhealthy behaviors has been described, identifying snacking children as having a sedentary lifestyle and spending the majority of leisure time alone [9]. However, snacking is also related with social and group activities, as an accompanying activity during social meetings and after them [10]. Social pattern of interaction are of course very different when referred to adults than for children.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is a real interest promoting FV consumption and healthier diet among young children, since it has been shown that dietary habits in adults are widely determined by those adopted during childhood [ 53 , 54 ]. The FLAM study has been set in Saint-Denis city because of its greater precariousness and its increased cardiovascular diseases prevalence [ 28 , 32 , 33 ]. In 2013, according to the French National Statistic Institute (INSEE, Institut National de la Statistique et des études économiques ), the poverty rate of Saint-Denis raised up to 36.7% of the population, and a quarter (25.4%) of families were single-parent [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unemployment rate is high (17.5% of unemployed in 2014 vs. 10.4% in France) [ 28 ], as well as the poverty rate (38.7% vs 14.1% in France) [ [28] , [29] , [30] , [31] ]. In addition, the prevalence of diabetes for all ages was 5.42% in Seine-Saint-Denis (while it is 4.82% in France) [ 32 ], and the obesity rate was 13.9% in children aged 5 years old against 10.6% in France [ 33 ]. Single parenthood was initially a selection criterion, but given recruitment difficulties (see below), inclusions were then extended to families with two parents.…”
Section: Methodsmentioning
confidence: 99%